ENGORDE DE LLAMAS BAJO DIFERENTES REGÍMENES ALIMENTICIOS - García V., Wilber (2002)
The present study was carried out at IVITA-Maranganí Experimental Station to evaluate the animal response to fattening in llamas of two ages submitted to different nutritional regimes in two seasons. An irrestricted randomize design with 2 x 2 x 3 factorial arrangement (two ages: 1 and 2; two seasons: rainy and dry; and three nutritional regimes: natural pasture, mixture of phalaris + clover, and mixture ofryegrass + clover) was used. A total of 60 male llamas (30 of one year and 30 of two years old) were used during a 90-day period of fattening. The stocking rate was 5, 10 and 10 animals/ha for natural pasture, phalaris + clover, and ryegrass + clover, respectively. The body weight gain was evaluated at different periods: 0-30, 31-60, 61-90, 0-60 and 0-90 days (d). Differences in body weight gain was observed in llamas of two years old (183 g/d) as compared with those of one year of age (146 g/d; P<0.05) in the period 0-30d. Body weight gain was better during the rainy (l 7lg/d) than in the dry season (136 g/d; P< 0.05). The best nutritional regime was ryegrass + clover ( 199 g/d) and phalaris + clover ( 182 g/d) as compared to natural pasture (78 g/d; P<0.05). The largest body weight gain was in the period 0-60 d (178 g/d). The best economic merit were was obtained in the ryegrass + clover pasture (5.81 % ) and in phalaris + clover ( 4.29%) in the period 0-60 d. lt is concluded that the largest body weight gain and the best economic merit were achieved in cultivated pastures.